2015
DOI: 10.1089/lrb.2013.0054
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized Lymph Nodes as Scaffolds for Tissue Engineered Lymph Nodes

Abstract: Background: The lymphatic system is commonly injured during cancer treatment. However, despite the morbidity of these injuries, there are currently no options for replacing damaged lymphatics. The purpose of this study was to optimize methods for decellularization of murine lymph nodes (LN) and to determine if these scaffolds can be used to tissue engineer lymph node-like structures. Methods and Results: LNs were harvested from adult mice and subjected to various decellularization protocols. The degree of dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
(21 reference statements)
0
20
0
Order By: Relevance
“…The utility of decellularized scaffolds has widely focused on the tendon, bladder, blood vessels, kidney, and lung, but few on the lymph node [30,31,32]. Cuzzone et al demonstrated that lymph nodes could be decellularized by sodium dodecyl sulfate treatment, successfully eliminating the cellular material and preserving the ECM [16]. However, other common decellularized methods, such as TRITON-X and 3-[(3-cholamidopropyl) dimethylammonio]-1-propanesulfonate, were not effective when used in lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of decellularized scaffolds has widely focused on the tendon, bladder, blood vessels, kidney, and lung, but few on the lymph node [30,31,32]. Cuzzone et al demonstrated that lymph nodes could be decellularized by sodium dodecyl sulfate treatment, successfully eliminating the cellular material and preserving the ECM [16]. However, other common decellularized methods, such as TRITON-X and 3-[(3-cholamidopropyl) dimethylammonio]-1-propanesulfonate, were not effective when used in lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…It provides a strategy by which to fabricate lymph node scaffolds on which to grow immune cells with immunological function. Previous studies demonstrated that spleen-derived decellularized ECM or lymph node-associated decellularized ECM can deliver immune cells and promote the organization of lymphoid-like scaffolds [16,17]; however, whether these can induce antigen-specific immunity or the antitumor immune response is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The environment itself, the stroma, seems to be crucial. Implanted scaffolds with lymphoid tissue initiators, or implanting repopulated decellularized lymphoid organs, have presented some successful results in animal models. Engineering lymphoid stroma has also been pursued in vitro .…”
Section: Conclusion and Perspectives For The Futurementioning
confidence: 99%
“…Daniel et al engineered lymph nodes by using SDS to decellularize the lymph node of mice and repopulated it with leukocytes harvested from the spleen of another donor mouse. 2 Purwada et al first engineered gelatin hydrogels combined with polyionic silicate nanoparticles to encapsulate murine germinal center B cell clusters in 2D cultures. 3 However, there are no widely accepted techniques at present.…”
Section: Introductionmentioning
confidence: 99%